Homicide Patterns in Estonia During the 1994−2023 Period - Ahven, Andri (Journal of contemporary criminal justice, 2024)
This article describes patterns in the homicides committed in Estonia since the 1990s. The overall decreasing trend in mortality is first described using mortality statistics. Based on a dataset of court verdicts spanning the 2016−2023 period, we extend previous research in this domain by describing current homicide patterns. To reflect on changes, we compare the results yielded by our investigation with those obtained in prior key studies. According to our analyses, mortality due to homicide exhibited a relatively stable trend over the last decade, with alcohol as a major contributor to most of these incidents. At the same time, there has been a decrease in economically motivated cases, as well as in homicides committed with firearms. Guided by these results, we provide suggestions for future research aimed at contributing to the European Homicide Monitor (EHM) database.